Pemberdayaan Masyarakat Melalui Kegiatan Economic Project Olahan Fish Corndog di Desa Pasir Panjang, Pulau Rinca, NTT - Putri, Atfi Indriany; Badi’ah, Roudlotul; Putera, Muhammad Ikbal; Ikhlas, Fahri; Umar, Arni Putri Awaliyah (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to diversify processed fishery products as regional souvenirs to attract tourists and increase the selling value of fishery products in Pasir Panjang Village, Rinca Island, West Manggarai Regency, East Nusa Tenggara (NTT) Province. The method used in this service program is counselling and training with a participatory approach. Implementation of service activities includes survey and administration stages, Focus Group Discussion (FGD), implementation, and evaluation based on success indicators determined. The result of this community service activity was the creation of an innovative processed fishery product called "Fish Corndog," which can be used as a souvenir as a typical food product from Pasir Panjang Village, thus helping to increase its attractiveness in the eyes of tourists and ultimately contributing to improving the economy of the surrounding community. Apart from that, a Social Sector PKK Women’s Group was also formed to re-socialize the processing of processed Fish Corndog products.